Gram-scale synthesis, in silico analysis, and antimicrobial potential of phytoalexins camalexin, N-methylcamalexin, including their novel methylated analogues - Yordan Stremski; Maria Bachvarova; Stela Statkova-Abeghe; Bogdan Goranov; Zlatka Ganeva (Natural Product Research, 2026)

EurOP2E – the European Open Platform for Prescribing Education, a consensus study among clinical pharmacology and therapeutics teachers - Michiel J. Bakkum; Milan C. Richir; Paraskevi Papaioannidou; Robert Likic; Emilio J. Sanz; Thierry Christiaens; João N. Costa; Romaldas Mačiulaitis; Lorena Dima; Jamie Coleman; Jelle Tichelaar; Michiel A. van Agtmael; et al. (European Journal of Clinical Pharmacology, 2021)
Purpose Sharing and developing digital educational resources and open educational resources has been proposed as a way to harmonize and improve clinical pharmacology and therapeutics (CPT) education in European medical schools. Previous research, however, has shown that there are barriers to the adoption and implementation of open educational resources. The aim of this study was to determine perceived opportunities and barriers to the use and creation of open educational resources among European CPT teachers and possible solutions for these barriers. Methods CPT teachers of British and EU medical schools completed an online survey. Opportunities and challenges were identified by thematic analyses and subsequently discussed in an international consensus meeting. Results Data from 99 CPT teachers from 95 medical schools were analysed. Thirty teachers (30.3%) shared or collaboratively produced digital educational resources. All teachers foresaw opportunities in the more active use of open educational resources, including improving the quality of their teaching. The challenges reported were language barriers, local differences, lack of time, technological issues, difficulties with quality management, and copyright restrictions. Practical solutions for these challenges were discussed and include a peer review system, clear indexing, and use of copyright licenses that permit adaptation of resources. Conclusion Key challenges to making greater use of CPT open educational resources are a limited applicability of such resources due to language and local differences and quality concerns. These challenges may be resolved by relatively simple measures, such as allowing adaptation and translation of resources and a peer review system.